A method for identifying pigskin content in leather products. - Che Man, Yaakub; Mphd Zaki, Mohd Hafiz; Saeed Mirghani, Mohamed Elwathig; Zainul Abidin, Shahariza (2008)
Recent discovery of non-Halal products being sold to the public without clear description of its status has propted Muslims to be more sensitive in choosing these items. Because of this concern, it is crucial to develop methods of detection for non-Halal leather. In this study, an analytical technique for determination of pigskin leather is conducted. Leather products from different origins including cow, goat, sheep and pig were used. Scanning Electron Microscope (SEM) was used to identify the characteristics of pigskin leather as source of non-Halal leather based on the grain surface and cross section of leather samples. Fourier Transform Infrared (FTIR) spectoscopy is used to obtain mid infrared (IR) spectra at wavenumber region of 4000cm⁻? to 400 cm⁻?. the differentation between leather and non-halal leather from FTIR analysis is based on three region of interest from the spectra obtained. The regions are 1200- 1000cm⁻?, 700 - 600 cm⁻? and 500 - 400 cm⁻?. the regions can be proposed and applied as a standard for leather determine leather products made from pigskin or skin of other animal species. The result of this study could also be used to distinguish leather, non-leather or imitation leather products.